PERSEPSI ORANG TUA TERHADAP PEMBELAJARAN DARING PADA SISWA KELAS VII SMP NEGERI 1 BANGKINANG KABUPATEN KAMPAR - Oktavia, Rini; Supentri, Supentri; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : This research was motivated by a phenomenon that emerged based on a pre-survey that the researchers conducted earlier at the end of October 2020 at the parents' homes of SMP Negeri 1 Bangkinang students. The formulation of the problem in this study is how the perception of 7th grade parents of SMP Negeri 1 Bangkinang, Kampar Regency. The purpose of this study was to find out how the perception of 7th grade parents of SMP Negeri 1 Bangkinang, Kampar Regency. The benefits of this research are that it is expected to provide additional information for all parties, especially parents in responding to online learning carried out by students. This research method is descriptive quantitative. The population in this study were the parents of 7th grade students of SMP Negeri 1 Bangkinang, totaling 107 parents and a sample of 52 respondents determined by incidental sampling technique. Data collection instruments are questionnaires, and interviews. Based on the results of the research conducted, it can be concluded from the overall data regarding parents' perceptions of online learning in 7th grade students of SMP Negeri 1 Bangkinang is at the level of "Poor". Very Good amounted to 5.53% plus good results with a total of 32.85%, namely the total result was 38.35% with a range of 25.01% - 50%. Thus, the parents' perception of online learning in Grade VII students of SMP Negeri 1 Bangkinang, Kampar Regency is at the "Poor Good" level.Key Words: Perception, Parents, Online Learning.